If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1x = 3x + 7 Reorder the terms: 9 + -1x = 7 + 3x Solving 9 + -1x = 7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9 + -1x + -3x = 7 + 3x + -3x Combine like terms: -1x + -3x = -4x 9 + -4x = 7 + 3x + -3x Combine like terms: 3x + -3x = 0 9 + -4x = 7 + 0 9 + -4x = 7 Add '-9' to each side of the equation. 9 + -9 + -4x = 7 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = 7 + -9 -4x = 7 + -9 Combine like terms: 7 + -9 = -2 -4x = -2 Divide each side by '-4'. x = 0.5 Simplifying x = 0.5
| 117-9r=36 | | 138=6(5r-2) | | 2(3x+5)-2(3x-2)=8 | | 3/2(x)-1/2=x+7/6 | | u/31+587=597 | | 172=-4(8x-3) | | 178-6u=940 | | xy-5x-5y-7=0 | | 2x+12+2x+4x=180 | | -2.11=x-3.7-6.3x | | 6x+47=8x*31 | | (11x+1)(8y+9)=14 | | 4x^2+bx+24=0 | | 6m*6m*6m=0 | | 30=-5(6n+5) | | -32=-6(3s+9) | | 4.2=a+6.4+1.1 | | -16x^2+143x+9=0 | | 13x-20=5x+36 | | x^2+50x+464=0 | | 1n+2n=6 | | -16x^2+143t+9=0 | | 1n+2n=5 | | -4-7k=-12-6k | | (-26)+31= | | 328=x-31+219 | | -0.18x+y=-6.54 | | n^2-n+2.5=200 | | 6r-2r+6r=r | | -13=1+7v+7v | | 13=5(1+2n)-4(n-4) | | -481=-15j-61 |